Using Institutional Planning to Support Men of Color in Community College. Issue 4 (3rd April 2022) - Felix, Eric R.; Gonzalez, Ángel
ABSTRACT: Recent years have brought an increasing amount of attention to the educational experiences and outcomes for men of color. As a group, these students experience some of the lowest rates of success in community college. These inequities in education start early, fueled by racial/gender dynamics, stereotyping, and growing up in under-resourced communities. With these known barriers facing men of color, there are few policy initiatives developed explicitly to address these students. More generally, states have passed reforms to improve completion and attainment that may support men of color. This paper examines California's Student Equity Policy (SEP), an initiative seeking to mitigate equity gaps in community college, to see if and how implementation benefits men of color in community college. The policy required community colleges to assess inequities by race and gender as well as other demographics to identify gaps in success then develop a student equity plan with goals and solutions to mitigate them. Through critical policy analysis, the authors document the opportunities in these equity plans to address men of color by examining 42 community colleges in the state. Although men of color were identified 33% of the time as facing inequity, we found only 6% of activities in these plans explicitly addressed them. Based on these results we provide promising practices that offer ways to support men of color in community college and conclude with recommendations to better utilize policy as a tool to improve the equity gaps for these students.